Spunti filosofico-giuridici sull’amore. A proposito delle unioni civili (Stato, Chiese e pluralismo confessionale, 2016)
Il contributo, sottoposto a valutazione, riproduce il testo della Relazione al Convegno di studio dal titolo Modelli di famiglia. Tra matrimonio tradizionale e unioni dello stesso sesso, presso LUM “Jean Monnet” (Trani, 21 aprile 2016).SOMMARIO: 1. Posizione del problema: alla ricerca di una comune matrice metodologica – 2. Una possibile giustificazione: il mito dell’androgino – 3. L’amore è (anche) un diritto? – 4. Conclusioni.ABSTRACT: The debate concerning the rights and the duties of the same-sex couples is at the centre of the public discourse. It is, in fact, no longer confined to the life situations of the persons involved in homosexual relations. According with a classical perspective, which is in particular based on the Francesco Carnelutti’s thought, this essay tries to demonstrate that the link between the feeling of love and a juridical system – which seems now to be taken for granted – could be dangerous. As matter of fact, the Author thinks that the distinction between those two spheres (love and juridical systems) is necessary, if not a prerequisite, for the right affirmation of the principle of equality.